Why, why, why, Delilah? New perspectives on the aetiology of intimate partner stalking - Creamer, C. J. (The journal of forensic psychiatry & psychology, 2025)
The ending of an intimate relationship, or the threat of separation, appears to elicit a catastrophic primal response in some individuals that can be a harbinger to lethal violence. Attachment theory, or a pathology of attachment, is established in the empirical literature as being a leading theory to explain Intimate Partner Stalking (IPS), though it is far from established what a ‘pathology’ of attachment represents. Since an earlier paper by Meloy and Fisher (2005) reflecting on the neurobiology of attachment, there has been limited attention to this in the empirical research. This paper reviews the evidence that attachment is not so much of a theory as a biological imperative, which, when broken down to the relevant quantities, can be reliably measured. The neurological substrates of the formation of interpersonal relationships provide a good starting point in understanding the process of IPS, and the Behavioural Systems Theory proposed by Bowlby is described from its evolutionary purpose as functional to protect the individual from danger by keeping them in close proximity to a caregiver (attachment figure). This in-turn can result in fixated behaviour such as IPS. Implications for legal sanctions against perpetrators of IPS (the assumption that they can stop), clinical management, and future research are discussed.